The Significance of Online Games: Their Influence on the Motivation of Islamic Religious Education (PAI) Students - Mauzifa; Siti Husna Ainu Syukri; L. Ahmad Didik Meiliyadi; M. Taisir (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to determine the impact of online games on the learning motivation of students in the Islamic Religious Education (PAI) Study Program at the Mataram State Islamic University (UIN Mataram). The method used is a quantitative method with a positivism approach, which involves numerical data and analysis of phenomena that occur. This type of research is ex post facto, which is carried out empirically and systematically. This research was conducted on third semester students class of 2021 at the PAI UIN Mataram Study Program who played online games. Data was collected using a Likert scale questionnaire to measure the influence of online games on learning motivation, as well as through observation and interviews. The initial hypothesis of the research states that there is a significant influence of online games on the learning motivation of third semester students at the PAI UIN Mataram Study Program. This research is a population study, and data analysis was carried out using parametric statistical tests from inferential statistics, using simple linear regression to test hypotheses. The results of the regression equation Y = 102,223 + (-0.35)X show that when variable X (online games) has a value of 0, variable Y (learning motivation) has a value of 102,223. A negative coefficient of -0.35 indicates that every 1% increase in variable X will reduce variable Y by 0.35. This means that the more often students play online games, the more their learning motivation decreases. A significance value of 0.000, which is smaller than 0.05, indicates that the alternative hypothesis is accepted, which means that there is a significant influence of online games on the learning motivation of third semester students at the PAI UIN Mataram Study Program. The correlation value (R) of 0.556 and R Square of 0.31 shows that online games have a 31% influence on learning motivation, while 69% is influenced by other factors.